Temporomandibular disorder, body pain and systemic diseases: assessing their associations in adolescents - Guilherme Vinícius do Vale BRAIDO; Leticia Bueno CAMPI; Paula Cristina JORDANI; Giovana FERNANDES; Daniela Aparecida de Godoi GONÇALVES (University of São Paulo, 2020)
Abstract Painful temporomandibular disorders (TMD) in children and adolescents may impact negatively the individual´s life. The presence of comorbidities associated with TMD tends to increase the persistence of pain and to facilitate its chronification. Objective To investigate the presence of other painful conditions and systemic diseases and their association with painful TMD. Methodology In this cross-sectional study, 690 adolescents aged between 12-14 years old were evaluated through questionnaires and clinical examinations. Results Painful TMD was found in 16.2% of the sample, with a significant association with bronchitis (OR= 2.5; p=0.003) and asthma (OR=3.1; p=0.013), reported by the parents/legal guardians of the participants. Adolescents with regional and widespread pain were 2.7 (95% CI: 1.65-4.55) and 3.6 (95% CI: 1.29-10.14) more likely to also present painful TMD. Painful TMD was associated with a higher number of body pain sites in the last 12 months (4.26 vs. 2.90; p<0.001), as well as a higher number of systemic diseases (1.48 vs. 1.18; p=0.048), when compared to adolescents without painful TMD. Conclusion The findings of this study point out the importance of considering the presence of comorbid conditions in the diagnosis and management of painful TMD in adolescents. A multidisciplinary approach would contribute to better control of painful TMD and decrease its chronification risk.